Some Hormonal Changes in Women with Primary Hypothyroidism under the Effect of Thyroid Hormone Replacement Therapy - Zainab S. Jabbar; Kassim J. Al-Shamma; Mohammad A. Taher (College of Pharmacy University of Baghdad, 2017)
Hypothyroidism has been associated with disorders of glucose and insulin metabolism..The present study was designed to evaluate the possible change in some hormones (free testosterone, estradiol, prolactin, insulin), glucose and homeostasis model assessment of insulin resistance (HOMA-IR) in women with primary hypothyroidism under thyroid hormone replacement therapy .This cross-sectional study was carried on 62 hypothyroid patients×³  women and 22  healthy women as control group at the specialized center for endocrinology and diabetes, AL-Rasafa Directorate of  Health Baghdad, with age range(15-60 years), diagnosed as having primary hypothyroidism on thyroxine replacement therapy with duration not less than four months. Each of the selected patients women and the healthy control were distributed into two groups, normal cyclic and postmenopausal. Blood samples were collected to measure thyroid stimulating hormone(TSH), total thyroxine (TT4) , total triiodothyronine (TT3), free thyroxine(fT4), free testosterone (FT), estradiol(E2) ,prolactin(PRL), insulin , fasting blood glucose( FBG), homeostasis model assessment-insulin resistance(HOMA-IR).  The results showed that the majority of hypothyroid women (older than 40 years and obese) had high levels of TSH in normal cyclic and postmenopausal patients women. A significant increase in f T4 and TT4 in postmenopausal patients women when  compared with postmenopausal control group f T4 and TT4.  A significant increase in free testosterone and FBG and significant decrease in TT3 and E2 levels in normal cyclic patients women when compared with normal cycle control group. High prolactin levels were found in the normal cyclic patients women in comparism with control group. Higher levels of insulin were found in normal cyclic and postmenopausal patients women as compared with control groups, however insulin was not statistically different. Significant increase in HOMA-IR  of  normal cyclic patients women compared with control group. In conclusion, elevation of TSH levels in postmenopausal patients women  were less than in normal cyclic patients women this explain the increase levels of thyroxine hormone(T4)in this group of patients as compared with both control group and normal cyclic patients women. Some hormonal changes were found in normal cyclic hypothyroid patients women as compared with control group.The alteration of these hormones disappear when euthyroid state restored, so adjustment of thyroxine therapy is required in these patients. Key words: Hypothyroidism , Thyrid replacement therapy.